Profits versus losses in caged aquaculture rearing: the case of entrepreneurs in Pekan, Pahang - Idris, Khairuddin; Azman, Azmariana; Alby, Jeffrey Lawrence D'Silva; Man, Norsida; Mohamed Shaffril, Hayrol Azril (Universiti Putra Malaysia, 2012)
The main attempt of this study is to identify the benefits and problems faced by entrepreneurs of caged aquaculture rearing in Pekan Pahang. This study is qualitative in nature where two FGDs have been conducted to gain the needed data. The FGDs have been joined by a total of 12 respondents; five respondents for FGD conducted at Tanjong Gosong and seven respondents for FGD in Pulau Keladi Village. The selected respondents were the entrepreneurs of caged aquaculture rearing from two villages in Pekan Pahang which were Pulau Keladi Village and Tanjung Gosong Village. For the benefits of aquaculture activities, four main themes have emerged namely increasing their income, sense of hard work, creativity to vary alternatives in solving problems and norm of cooperation. In term of problems faced by the entrepreneurs, four main themes namely financial, environments, seedling and diseases and human and animal factors have emerged.